Atlas of the ethno-political history of the Caucasus - T︠S︡ut︠s︡iev, A. A. (Artur Arkadʹevich)
Offers a collection of fifty-six original maps with commentaries that detail the ethnic, religious, and linguistic makeup of the Caucasus - the region located between the Black and Caspian Seas that contains Europe's highest mountain - from the eighteenth century to the present